HARMONIZING LEGAL PLURALISM IN JUVENILE JUSTICE: A SYNERGISTIC REHABILITATION MODEL FOR ACEH’S LPKS AND LPKA - Liza Agnesta Krisna; Rini Fitriani; M. Iqbal Asnawi; Muhammad Iqbal (Universitas Syiah Kuala, 2026)
This study examines the imperative for a synergistic rehabilitation model between Social Welfare Organizing Institutions (LPKS) and Juvenile Special Development Institutions (LPKA) for children in conflict with the law (CICL) within Aceh’s unique pluralistic legal framework. The article addresses how institutional fragmentation characterized by overlapping functions and inconsistent approaches between the social welfare and penal systems undermines the effectiveness of child rehabilitation. Using a normative-empirical method, the study combines a rigorous analysis of national legislation, such as Law No. 11 of 2012, with field findings from observations and interviews conducted across multiple judicial and social institutions in Aceh.The results reveal significant systemic gaps in inter-agency coordination, legal harmonization, and continuity of care between pre- and post-adjudication stages. In response, this study proposes a six-dimensional integrative model focused on legal alignment, institutional strengthening, scalability, and implementation planning. This model emphasizes the development of integrated data systems and shared standard operating procedures to ensure seamless case management. The findings suggest that a child-centered, restorative justice approach, firmly grounded in the principles of maqashid shariah, can reconcile the tensions between national child protection standards and Aceh’s autonomous Qanun system. By prioritizing the best interests of the child and social reconciliation (islah), this model provides a practical framework for sustainable reintegration, to improve institutional coordination and ensure a more holistic, culturally sensitive juvenile justice system.